Ekofeminisme Kritis: Menelaah Ulang Gender, Keadilan Ekologi, dan Krisis Iklim - Ayom Mratita Purbandani; Rangga Mahaswa (Yayasan Jurnal Perempuan, 2022)
Ecofeminism as an intellectual theory is often criticized for its incoherency in the body of thinking. Thus, ecofeminism is reputed as promising nothing transformative and adequate in answering the challenges of multiple ecological destructions, including climate crisis. However, the trajectories and influences of ecofeminism can’t be denied—from ethical debates to policies. Therefore, this research invites us to think about ecofeminism from a critical perspective without perpetuating patriarchal stereotypes and essentialism. The critical ecofeminism approach is an offer from writers to help to understand and portray gender-affected climate change impacts.